A biallelic pathogenic variant in the OGDH gene results in a neurological disorder with features of a mitochondrial disease. Issue 2 (24th June 2020) - Yap, Zheng Yie; Strucinska, Klaudia; Matsuzaki, Satoshi; Lee, Sukyeong; Si, Yue; Humphries, Kenneth; Tarnopolsky, Mark A.; Yoon, Wan Hee
Abstract: 2‐Oxoglutarate dehydrogenase (OGDH) is a rate‐limiting enzyme in the mitochondrial TCA cycle, encoded by the OGDH gene. α‐Ketoglutarate dehydrogenase (OGDH) deficiency was previously reported in association with developmental delay, hypotonia, and movement disorders and metabolic decompensation, with no genetic data provided. Using whole exome sequencing, we identified two individuals carrying a homozygous missense variant c.959A>G (p.N320S) in the OGDH gene. These individuals presented with global developmental delay, elevated lactate, ataxia and seizure. Fibroblast analysis and modeling of the mutation in Drosophila were used to evaluate pathogenicity of the variant. Skin fibroblasts from subject # 2 showed a decrease in both OGDH protein and enzyme activity. Transfection of human OGDH cDNA in HEK293 cells carrying p.N320S also produced significantly lower protein levels compared to those with wild‐type cDNA. Loss of Drosophila Ogdh ( dOgdh ) caused early developmental lethality, rescued by expressing wild‐type dOgdh ( dOgdh WT ) or human OGDH ( OGDH WT ) cDNA. In contrast, expression to the mutant OGDH ( OGDH N320S ) or dOgdh carrying homologous mutations to human OGDH p.N320S variant ( dOgdh N324S ) failed to rescue lethality of dOgdh null mutants. Knockdown of dOgdh in the nervous system resulted in locomotion defects which were rescued by dOgdh WT expression but not by dOgdh N324S expression. Collectively, the results indicate that c.959A>G variant in OGDH leads to an amino acid change (p.N320S) causing a severe loss of OGDH protein function. Our study establishes in the first time a genetic link between an OGDH gene mutation and OGDH deficiency.